Peran Pembiayaan Bank Syariah Indonesia (BSI) Gatot Subroto Kota Jambi terhadap Pertumbuhan Usaha Kecil dan Menengah Tahun 2020-2023 - Darni Krisnawati Lase; Agustina Mutia; G.W.I. Awal Habibah (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Bank Syariah Indonesia is a bank whose procedures are carried out in accordance with Islamic law. Bank Syariah Indonesia is a merger of BRI Syariah, BNI Syariah and Bank Mandiri Syariah which was inaugurated on February 1, 2021 or 19 Jumadil Akhir 1442 H. KUR financing is one of the products offered by BSI KC Gatot Subroto Jambi City to Micro, Small and Medium Enterprises (MSMEs). This study aims to determine the role of BSI in developing MSMEs in Jambi City. To determine the development of MSMEs after receiving financing from BSI and what factors cause the increase in the MSME economy in Jambi City. The research used by the researcher is a qualitative method, namely conducting observations, interviews and documentation with sources and collecting documentation in the form of documents related to financing. The data sources used by the researcher are primary data from the first source and secondary data from the second source. The results of this study indicate that: BSI has played a role in developing MSMEs in Jambi City by providing additional capital. Factors that have led to the increase in MSMEs in Jambi City are that BSI KCP Gatot Subroto makes it easier for customers to use KUR financing products and Micro, Small, and Medium Enterprises maximize the capital obtained. The implementation of BSI financing in increasing MSME businesses in Jambi City has been carried out in accordance with procedures, namely providing financing to customers who meet the requirements of BSI KC Gatot Subroto.